Empirismus und Ästhetik Zur deutschsprachigen Rezeption von Hume, Hutcheson, Home und Burke im 18. Jahrhundert - Knapp, Lore (Hallesche Beiträge zur Europäischen Aufklärung, 2022)
Francis Hutcheson, David Hume, Edmund Burke, and Henry Home combined empiricism and aesthetics to create an empiricist aesthetics that was received and transformed in the German-speaking world. In the tradition of John Locke, an explanation of thinking and association that is grounded in sensualism takes center stage.